THE PROBABILITY OF THE PRINCIPAL'S LEADERSHIP PROFESSION IN THE PERSPECTIVE OF EDUCATION MANAGEMENT TO RESPOND TO CHALLENGES IN THE 5.0 ERA - Bahdin Nur Tanjung (Hijri, 2023)
Â The purpose of this article is to explain education management, the profession of the school principal plays a very important role in ensuring the success of an educational institution. A school principal acts as a leader and manager, responsible for creating a conducive learning environment, managing resources, and ensuring the delivery of quality education. The method used in collecting data using library research or library research is a research method that is carried out by utilizing information sources available in the library, such as books, journals, articles, and other sources of information. The purpose of library research is to collect and analyze data or information about a topic or problem being researched. The results of the analysis of several reference sources reveal that school principals must have good leadership and management skills, and have extensive knowledge of the principles of education management. Principals must also be able to adapt to changes in the dynamic educational environment, and have the ability to lead and develop teaching staff and motivate students in achieving the desired educational goals. Thus, the principal can be the key to the success of an educational institution and play a role in shaping a better educational futureÂ Leadership, Education, Management